Implementing Lean Leadership in Garment Industries - Laith Al-Badareen (International Journal of Engineering and Management Sciences, 2018)
Garment industries are one of the most competitive industries nowadays, that was the main reason why implementing lean tools became conventional between big brands, although, lean tools alone are not enough for successful lean implementation in any organization, that’s why creating lean leaders and defining what lean leadership exactly means became a necessity, in this study, we will try to draw a path in which garment manufacturers can pursue to become lean organizations taking a (Manufacturer for NIKE) as an example for the study as a heavy lean implementer closing by suggesting a 9 steps method that lean can be implemented successfully in garment industry factory.